Enhanced mercury removal by transplanting sulfur-containing functional groups to biochar through plasma. (1st October 2019) - Zhang, Huicong; Wang, Tao; Sui, Zifeng; Zhang, Yongsheng; Sun, Baomin; Pan, Wei-Ping
Graphical abstract: Highlights: The C–S groups generated in the plasma promote the removal of mercury. The mercury removal efficiency of biochar increased from 26.4% to 95.5% after modification. Hg 0 is adsorbed on the modified sample to form HgS and HgO. Active S released from broken C–S bonds at high temperature reacts with Hg 0 in the gas phase. Abstract: Six biomasses (rice, tobacco, corn, wheat, millet and black bean straws) were used to prepare biochar. The mercury removal performance of the obtained biochars after H2 S plasma modification was tested, and characterisation was by FTIR (including in-situ FTIR), XPS and TPD. The mercury removal efficiency of biochar was enhanced after H2 S plasma modification. The initial efficiency of wheat straw biochar was raised from 26.4% to 95.5% after modification. The number of sulfur-containing and carboxyl functional groups on the surface of the biochar increased through plasma modification. C–S and carboxyl are considered as the main functional groups forming HgS and HgO in mercury removal. The biochar after modification exhibited better mercury removal capacity at low temperatures. Active S is released from the C–S bonds at high temperature and further oxidises Hg 0 in the gas phase. The adsorption process of modified samples is controlled by physical and chemical adsorption at 30 °C, while the main part of the reaction at 150 °C takes place in the gas phase.